Basal localization of MT1-MMP is essential for epithelial cell morphogenesis in 3D collagen matrix - Weaver, SA; Wolters, B; Ito, N; Woskowicz, A; Kaneko, K; Shitomi, Y; Seiki, M; Itoh, Y (Company of Biologists, 2014)
The membrane-anchored collagenase membrane type 1 matrix metalloprotease (MT1-MMP) has been shown to play an essential role during epithelial tubulogenesis in 3D collagen matrices; however, its regulation during tubulogenesis is not understood. Here, we report that degradation of collagen in polarized epithelial cells is post-translationally regulated by changing the localization of MT1-MMP from the apical to the basal surface. MT1-MMP predominantly localizes at the apical surface in inert polarized epithelial cells, whereas treatment with HGF induced basal localization of MT1-MMP followed by collagen degradation. The basal localization of MT1-MMP requires the ectodomains of the enzyme because deletion of the MT-loop region or the hemopexin domain inhibited basal localization of the enzyme. TGFβ is a well-known inhibitor of tubulogenesis and our data indicate that its mechanism of inhibition is, at least in part, due to inhibition of MT1-MMP localization to the basal surface. Interestingly, however, the effect of TGFβ was found to be bi-phasic: at high doses it effectively inhibited basal localization of MT1-MMP, whereas at lower doses tubulogenesis and basal localization of MT1-MMP was promoted. Taken together, these data indicate that basal localization of MT1-MMP is a key factor promoting the degradation of extracellular matrix by polarized epithelial cells, and that this is an essential part of epithelial morphogenesis in 3D collagen.